A (Hetero)Topology of Rhetoric and Obama's African Dreams. Issue 1 (2nd January 2016) - Chirindo, Kundai
ABSTRACT: The emplacements of rhetoric are manifold and the inquiries into the topologies of rhetoric are ways of understanding developments in rhetorical theory. To these ends, I contrast in this article the invocations of place in rhetorical theory old and new. In this long view, the spatiality of rhetoric appears to be multifaceted. I show that in Greco-Roman rhetorical theory, spatiality is topical, figured metaphorically and literally, and functions as a precedent condition for rhetoric. I argue that modern/postmodern theories differ from traditional theories of rhetoric not because they rely more or less on the materiality or immateriality of place, but because of their orientations to place as heterotopic, that is, as fluid and contingent. I then offer an account of how heterotopic rhetoric challenges orders of knowledge allowing for ever-new articulations through a close reading of Barack Obama's Dreams from my Father . The heterotopology of rhetoric proposed here expands understandings of the heuristic function of place. The essay considers the implications heterotopic place holds for identity and subjectivity.